2014
DOI: 10.1371/journal.pone.0110273
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Promotes Human Umbilical Vein Endothelial Cell Proliferation through the ERK Signaling Pathway and Partly Suppresses High Glucose-Induced Apoptosis

Abstract: Irisin is a newly discovered myokine that links exercise with metabolic homeostasis. It is involved in modest weight loss and improves glucose intolerance. However, the direct effects and mechanisms of irisin on vascular endothelial cells (ECs) are not fully understood. In the current study, we demonstrated that irisin promoted Human Umbilical Vein Endothelial Cell (HUVEC) proliferation. It was further demonstrated that this pro-proliferation effect was mediated by irisin-induced activation of extracellular si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
98
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 27 publications
9
98
1
1
Order By: Relevance
“…Inhibition of p38 mitogen-activated protein kinase or Erk abolished the upregulatory effect of irisin on Ucp1 expression (31). This signaling pathway was also shown in human umbilical vein endothelial cells (32). However, we did not find the Erk pathway nor the Akt and JNK pathways changed by irisin treatment in hepatocytes.…”
Section: Discussionmentioning
confidence: 44%
“…Inhibition of p38 mitogen-activated protein kinase or Erk abolished the upregulatory effect of irisin on Ucp1 expression (31). This signaling pathway was also shown in human umbilical vein endothelial cells (32). However, we did not find the Erk pathway nor the Akt and JNK pathways changed by irisin treatment in hepatocytes.…”
Section: Discussionmentioning
confidence: 44%
“…For example, the rs145204276 located in the promoter region of GAS5 has been reported to be an endogenous competing RNA of miR-21 [23][24][25]. Also, PDCD4 is believed to play a critical function in the pathogenesis of atherosclerosis by modulating the apoptosis of vascular endothelial cells [26,27], while our in-silicon analysis also found that miR-21 virtually targeted PDCD4. In this study, we aimed to explore the role of GAS5, miR-21, and its target genePDCD4, in the control of apoptosis of endothelial cells.…”
Section: Introductionmentioning
confidence: 52%
“…Recent studies have demonstrated that irisin can promote cell proliferation and protect cells from high-glucose-induced damage[3]. However, the effects of irisin on pancreatic β cells are still unclear.…”
Section: Discussionmentioning
confidence: 99%